The Capacity of the Indonesian Healthcare System to Respond to COVID-19 - Mahendradhata, Yodi; Andayani, Ni Luh Putu Eka; Hasri, Eva Tirtabayu; Arifi, Mohammad Dzulfikar; Siahaan, Renova Glorya Montesori; Solikha, Dewi Amila; Ali, Pungkas Bahjuri (Frontiers in Public Health, 2021)
The Indonesian Government has issued various policies to fight COVID-19. However, cases have continued to fluctuate. There is a need to assess the country’s healthcare system’s capacity to absorb and accommodate the varying healthcare demands. We reviewed the current capacity of Indonesia’s healthcare system to respond to COVID-19 based on the four essential elements of surge capacity: staff, stuff, structure, and system. Currently available medical staff are insufficient to deal with potentially increasing demands as the pandemic highlighted the human resources challenges the healthcare system has been struggling with. The pandemic has exposed the fragility of medical supply chains. Surges in the number of patients requiring hospitalization have led to depleted medical supplies. The existing healthcare infrastructure is still inadequate to deal with the rise of COVID-19 cases, which has also exposed the limited capacity of the healthcare infrastructure to manage medical waste. The COVID-19 pandemic has further exposed the weakness of the patient referral system and the limited capacity of the healthcare system to deliver essential health services. There is an urgent need to secure standard protection and psychological and welfare support for healthcare professionals. Regionalization of COVID-19 responses to facilitate better distribution of healthcare professionals, medical supplies, equipment, and healthcare facilities, including medical waste treatment facilities, should be developed. Telemedicine should be scaled up to enable safer deployment of more healthcare professionals, reduce the use of limited personal protective equipment, and protect essential health services. Healthcare surge capacity should be regularly assessed and ensured.